NADPH Oxidases in Aortic Aneurysms - Morgan Salmon (MDPI AG, 2022)
Abdominal aortic aneurysms (AAAs) are a progressive dilation of the infrarenal aorta and are characterized by inflammatory cell infiltration, smooth muscle cell migration and proliferation, and degradation of the extracellular matrix. Oxidative stress and the production of reactive oxygen species (ROS) have been shown to play roles in inflammatory cell infiltration, and smooth muscle cell migration and apoptosis in AAAs. In this review, we discuss the principles of nicotinamide adenine dinucleotide phosphate oxidase (NADPH oxidase/NOX) signaling and activation. We also discuss the effects of some of the major mediators of NOX signaling in AAAs. Separately, we also discuss the influence of genetic or pharmacologic inhibitors of NADPH oxidases on experimental pre-clinical AAAs. Experimental evidence suggests that NADPH oxidases may be a promising future therapeutic target for developing pharmacologic treatment strategies for halting AAA progression or rupture prevention in the management of clinical AAAs.